Prepartum lameness on subsequent lactation in Holstein dairy cows - Barbosa,Antônio Amaral (2020)
ABSTRACT: The aim of this study was to confirm the possible consequences of prepartum lameness on subsequent lactation among Holstein cows. In this research, 27 multiparous cows, were monitored from the 30th to 63rd day, relative to calving. Thirty days prior to parturition, the animals were segregated into two groups based on the locomotion score (LS), where LS 1 is attributed to animals without claudication, LS 2 to those with suspected lameness and LS 3, 4 and 5 to those with mild, moderate and severe lameness, respectively; in the lame cows group (LC) (n=15), the animals displayed LS ≥ 3, whereas in the non-lame cows group (NLC) (n=12) they showed LS 1. Milk production, body condition score (BCS) and blood concentration levels of β-hydroxybutyrate (BHB), urea, phosphorus, calcium aspartate aminotransferase (AST), gamma glutamyl transferase (GGT) and total plasma proteins (PPT) were evaluated. Milk production (17.675 ± 0.31 L of milk/day) and blood calcium concentration (7.42 ± 0.12 mg/dL) were lower in the lame cows in comparison to those without lameness (22.27 ± 0.42 L of milk/day and 9.63 ± 0.13 mg/dL). Besides, the lame cows showed higher BCS loss during the early postpartum period. The metabolites AST, GGT, PPT, urea, BHB and phosphorus revealed no difference between the groups during the period evaluated. The lameness evident in cows during prepartum exerted major negative effects on the milk production and calcemia, making the LS evaluation during these period an important tool in the early diagnosis of losses for future lactation.